Evaluation of Antibiotic Use in Child Patients with Acute Respiratory Tract Infection (ARI) - Damanik, Nadya Anggraini; Rangkuti, Irma Yanti; Sulistiasari, Refi; Sari, Siti Kemala (PT Inovasi Pratama Internasional, 2025)
Background: Acute respiratory infections (ARI) are still a major cause of high morbidity and mortality, with more than 12 million cases per year worldwide. Indonesia is one of the countries with a high burden of ARI with 6 million cases. Antibiotic resistance in bacteria that causes ARI is also increasing, so it is important to evaluate the rationality of antibiotic use. Objective: To evaluate the use of antibiotics in pediatric patients with acute respiratory infections (ARI) using the Gyssens method at Medan Hospital. Methods: Descriptive research with Gyssens method. Results: The majority of patients were toddlers with an age range of 12-59 months (47.7%). Male (64.6%), and female (35.4%). The most common diagnosis was pneumonia with a percentage of 90.8%. Ceftriaxone injection (78.5%) was most commonly used. The Gyssens method showed that category 0 was 52.3%, IIA 24.6%, and IIIB 23.1%. Conclusion: The use of antibiotics in pediatric ARI patients at Medan Hospital is mostly rational.